2022
DOI: 10.1128/aac.00138-22
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vancomycin Trough Serum Concentrations and Clinical Outcomes in Children: a Systematic Review and Meta-Analysis

Abstract: To systematically evaluate the relationships between vancomycin trough serum concentrations and clinical outcomes in children using meta-analysis. Several databases, including PubMed, Elsevier, Web of Science, EMBASE, Medline, clinicaltrials.gov , the Cochrane Library, and three Chinese databases (Wanfang Data, China National Knowledge Infrastructure, and SINOMED), were comprehensively searched to obtain research articles on vancomycin use in children from inception through December 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Vancomycin AUC 0–24 :MIC has been shown to be the best predictor of efficacy in severe MRSA infections 10 . Although C min monitoring is no longer recommended to assess the efficacy of vancomycin, C min may be of value when assessing the risk for nephrotoxicity 5,10,21–23 . Two recent systematic reviews and meta‐analyses conducted in children demonstrated that vancomycin C min values ≥15 mg/L were associated with increased risk of nephrotoxicity 5,7,8,23,24 .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Vancomycin AUC 0–24 :MIC has been shown to be the best predictor of efficacy in severe MRSA infections 10 . Although C min monitoring is no longer recommended to assess the efficacy of vancomycin, C min may be of value when assessing the risk for nephrotoxicity 5,10,21–23 . Two recent systematic reviews and meta‐analyses conducted in children demonstrated that vancomycin C min values ≥15 mg/L were associated with increased risk of nephrotoxicity 5,7,8,23,24 .…”
Section: Discussionmentioning
confidence: 51%
“…10 Although C min monitoring is no longer recommended to assess the efficacy of vancomycin, C min may be of value when assessing the risk for nephrotoxicity. 5,10,[21][22][23] Two recent systematic reviews and meta-analyses conducted in children demonstrated that vancomycin C min values ≥15 mg/L were associated with increased risk of nephrotoxicity. 5,7,8,23,24 Within our data, approximately 10% of patients treated with vancomycin with at least two SCr levels developed AKI.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…CL serves as a crucial PK parameter, exerting a signi cant in uence on drug exposure levels. Nevertheless, the vancomycin CL in pediatric patients is typically much faster compared to adults, approximately 2.5 times greater [7,16,19] . Limited available data indicate that the vancomycin CL in Chinese pediatric patients ranges from 0.11 to 0.17 L/h•kg, which is notably higher than that observed in adults [20,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Như vậy duy trì nồng độ đáy ở mức từ 10 đến 15μg/mL có thể đảm bảo hiệu quả lâm sàng tốt nhất và tỷ lệ phản ứng có hại của thuốc là tương đối thấp và trong phạm vi có thể kiểm soát được. Nghiên cứu này cung cấp bằng chứng mạnh mẽ hỗ trợ rằng việc duy trì nồng độ đáy của vancomycin ở trẻ em ở 10 đến 15 μg/mL có thể cải thiện hiệu quả lâm sàng và giảm tỷ lệ tác dụng phụ [11].…”
Section: Bàn Luậnunclassified